Beauty and the brooding CEO - Hyland, Juliette (Harlequin romance, 2024)
"Tale as old as time... Trekking through snow to a billionaire's secluded mountainous estate isn't what art conservationist Cora expected when she took the job. However, the chance to review Everett Winthrope's private collection--fulfilling her father's final wish--is far too tempting... And, despite his scars, the brooding CEO is ever more so! As her boss, he's completely off-limits, but that doesn't stop Cora's pulse from racing. Yet it's clear Everett's fortress hides more than just himself. Could unveiling who he is really help him step out of the shadows...and into a future with Cora?" -page [4] of cover